Structural and pharmacological insights into cordycepin for neoplasms and metabolic disorders - Zhang, Jinming; Yang, Ziling; Zhao, Zhuo; Zhang, Nan (Frontiers in Pharmacology, 2024)
Cytotoxic adenosine analogues were among the earliest chemotherapeutic agents utilised in cancer treatment. Cordycepin, a natural derivative of adenosine discovered in the fungus Ophiocordyceps sinensis, directly inhibits tumours not only by impeding biosynthesis, inducing apoptosis or autophagy, regulating the cell cycle, and curtailing tumour invasion and metastasis but also modulates the immune response within the tumour microenvironment. Furthermore, extensive research highlights cordycepin's significant therapeutic potential in alleviating hyperlipidaemia and regulating glucose metabolism. This review comprehensively analyses the structure-activity relationship of cordycepin and its analogues, outlines its pharmacokinetic properties, and strategies to enhance its bioavailability. Delving into the molecular biology, it explores the pharmacological mechanisms of cordycepin in tumour suppression and metabolic disorder treatment, thereby underscoring its immense potential in drug development within these domains and laying the groundwork for innovative treatment strategies.